Nanoencapsulation of Maqui (Aristotelia chilensis) Extract in Chitosan–Tripolyphosphate and Chenopodin-Based Systems - Daniela Andrade; Francisca Maldonado-Bravo; Amador Alburquerque; Camilo Pérez; Alexander Gamboa; Nelson Caro; Mario Díaz-Dosque; Martin Gotelland; Lilian Abugoch; Cristian Tapia (Antioxidants, 2024)
Maqui berries contain a high percentage of anthocyanins with high antioxidant and anti-inflammatory capacity but that are unstable in the colonic site. Nanocarriers based on polysaccharides and/or proteins can protect against the degradation of anthocyanins. The aim of this study was the nanoencapsulation of maqui extract (ME) in chitosan–tripolyphosphate (CTPP-ME), chenopodin (CH-ME), and chenopodin–alginate (CHA-ME). A standardised ME was prepared and then encapsulated in the nanosystems. The physicochemical properties, encapsulation parameters, and the interactions of ME with the nanovehicles were characterised. The cyanidin-3-glucoside released and ORAC activity in phosphate buffer at pH 7.4 were evaluated. The content of ME was 8–9 mg of cyanidin-3-glucoside/g of extract. CTPP with ME at 3% obtained the highest encapsulation efficiency (EE = 91%), and no significant differences were observed in size (274–362 nm), PDI (0.5–0.7), and zeta potential (+34–+41 mV) when the concentration of ME changed from 1% to 5%. CH-ME was shown to be smaller (152 nm) than CTPP-ME, and CH-ME and CHA-ME showed lower EE (79% and 54%, respectively) than CTPP-ME. FT-IR revealed a stronger interaction of ME with CTPP-ME than with CH-ME. Both systems showed a significantly lower release than free ME, and the T50 value of CTPP-ME 3% (328 min) was higher than CH-ME (197 min). Both protected the ORAC activity of ME.